2016
DOI: 10.1021/acs.jpcc.6b00384
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Scale Insights into the Early Stages of Metal Oxidation: A Scanning Tunneling Microscopy and Spectroscopy Study of Cobalt Oxidation

Abstract: Understanding the mechanisms driving the early stages of oxidation of metallic surfaces is of fundamental importance in fields such as nanocatalysis, electrochemistry, and nanoelectronics. In this work, the early stages of oxidation of ultrathin Co films deposited on the Fe(001)-p(1 × 1)O surface have been investigated by means of Auger electron spectroscopy, scanning tunneling microscopy, and scanning tunneling spectroscopy. The oxidation is initiated by homogeneous oxide nucleation over the atomically flat C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 81 publications
1
7
0
Order By: Relevance
“…These STM investigations clearly show the necessity of sample annealing up to 575 K to produce high quality Co films on Au(111) with large atomically flat terraces. While similar changes in surface morphology were also reported for ultrathin ferromagnetic films grown on different single crystalline surfaces such as Ru(0001) [41] and Fe(001) [42], our results show that this thermal activation procedure can also be extended to bulk-like ferromagnetic films.…”
Section: Growth Morphology and Chemical Composition Of Co Films On Asupporting
confidence: 87%
“…These STM investigations clearly show the necessity of sample annealing up to 575 K to produce high quality Co films on Au(111) with large atomically flat terraces. While similar changes in surface morphology were also reported for ultrathin ferromagnetic films grown on different single crystalline surfaces such as Ru(0001) [41] and Fe(001) [42], our results show that this thermal activation procedure can also be extended to bulk-like ferromagnetic films.…”
Section: Growth Morphology and Chemical Composition Of Co Films On Asupporting
confidence: 87%
“…A more detailed explanation of the tunneling mechanism is given in Chapter 3, Supporting Information. This behavior was observed, for example, for CoO islands on Ag(100) [ 25 ] and Pt(111), [ 26 ] for a thin CoO layer on Fe(001), [ 27 ] and for NiO on Ag(100). [ 24 ] In contrast to the BL, the apparent height of the DL features is independent of the bias voltage.…”
Section: Resultsmentioning
confidence: 93%
“…17 In particular, the CoO/Fe(001) interface has been a workbench for many investigations related to AF/FM systems with reactive interfaces, ranging from the exchange bias mechanism, 14,18 to the influence of structure and stoichiometry on the magnetic properties, 19 to the realization of peculiar magnetic configurations, like vortices. 20 Very recently, we have demonstrated that it is possible to prepare a CoO/Fe(001) interface characterized by the absence of any Fe oxide, 21,22 which is a quite unique feature with respect to the common experimental situations. 10,19,23 This result has been accomplished by exploiting an ultra-thin Co buffer layer with a bct cubic structure.…”
mentioning
confidence: 99%